MITIGATION OF DAMAGE TO VANAME SHRIMP (Litopenaeus vannamei) GILL TISSUE DUE TO Vibrio parahaemolyticus INFECTION THROUGH THE IMMUNOSTIMULANT Spathoteredo obtusa FROM SIDOARJO, EAST JAVA - Furqan, Andi Al (Directorate of Research and Community Service (DRPM), 2025)
One mitigation strategy that can be implemented for shrimp infected with vibriosis is the administration of immunostimulants. However, the use of commercial immunostimulants derived from chemical compounds is a cause for concern due to potential long-term adverse effects. This study focuses on gill tissue damage, survival rates, and water quality. The objective of this study is to determine the effect of administering natural immunostimulants from S. obtusa on gill tissue damage, survival rate, and water quality in vanamei shrimp infected with the bacteria V. parahaemolyticus. The study was conducted using vanamei shrimp samples divided into 7 treatments, each containing 10 shrimp. The treatments consisted of administering S. obtusa immunostimulant at 300 ppm (A), 400 ppm (B), 500 ppm (C), 600 ppm (D), 700 ppm (E), positive control (K+) as a treatment without S. obtusa immunostimulant administered and infected with V. parahaemolyticus, and a negative control (K-) as normal shrimp. The lowest level of lamella fusion damage was 5%, and the highest was 30%. The lowest level of lamella fusion damage was 5%, and the highest was 70%. The highest survival rate was 90.00%, and the lowest was 56.67%. The results indicate that mitigation efforts using the immunostimulant extract of S. obtusa from Sidoarjo, East Java, have a significant effect